Chronicles in Stone : Preservation, Patriotism, and Identity in Northwest Russia - Donovan, Victoria, 1981- (Book collections on Project MUSE., 2019)
"The book's central argument is that the Soviet state exploited the cultural heritage of the Northwest to craft patriotic narratives of the people's genius, heroism and strength that could bind the nation together after 1945"--